Overview of Targeted Drugs for Mature B-Cell Non-hodgkin Lymphomas - Crisci, Stefania; Di Francia, Raffaele; Mele, Sara; Vitale, Pasquale; Ronga, Giuseppina; De Filippi, Rosaria; Berretta, Massimiliano; Rossi, Paola; Pinto, Antonio (Frontiers in Oncology, 2019)
Background: The improved knowledge of pathogenetic mechanisms underlying lymphomagenesis and the discovery of the critical role of tumor microenvironments have enabled the design of new drugs against cell targets and pathways. The Food and Drug Administration (FDA) has approved several monoclonal antibodies (mAbs), and Small Molecules Inhibitors (SMIs) for targeted therapy in hematology. This review focuses on the efficacy results of the currently available targeted agents and recaps the main ongoing trials in the setting of mature B-Cell non-Hodgkin lymphomas Objective To resume the different classes of novel agents approved for mature B-cell lymphomas, to describe in synoptic tables the results they achieved and, finally, to draw future scenarios as they glimpse through the ongoing clinical trials. Characteristics and therapeutic efficacy are summarized for the currently approved mAbs (i.e., anti Cluster of Differentiation (CD) mAbs, Immune Checkpoint Inhibitors, Chimeric Antigen Receptor (CAR) T-Cell Therapy, bispecific antibodies) as well as for SMIs (i.e., inhibitors of B-cell Receptor signaling, proteasome, mTOR BCL-2 HDAC pathways. Future outlook The biological disease profiling of B-cell lymphoma subtypes may foster the discovery of drugs innovative strategies for improving survival outcome in lymphoid neoplasms, as well as the trade-offs between efficacy and toxicity. The hope for clinical advantages should carefully be coupled with mindful awareness of the potential pitfalls and the occurrence of uneven, sometimes severe, toxicities.